THE COMPLEXITY AND CHARACTERISTICS OF CHORAL ART - Luminiţa GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
The artistic act must be expressed technically and interpretatively. In the process of interpretation of a choral work, the conductor’s mission is to attain a unity between the technical and artistic aspects. Attaining this unity is possible only when the conductor has established a mental approach of the work (the Technical Mental Approach and the Performing Mental Approach), which they can achieve after going through two stages: The syntactical – morphological analysis (SMA) and the Choral – Vocal Analysis (CVA).